Significance of endothelin on volume homeostasis in obese Zucker rats - Wongmekiat O. (2014)
1. The present study explored the impact of endothelin (ET) and its interaction with renal sympathetic nerves in the control of volume homeostasis in obesity. 2. Groups of lean and obese Zucker rats with innervated and denervated kidneys were subjected to an acute isotonic saline volume expansion (VE), 10% bodyweight and renal haemodynamics and excretory function were evaluated following administration of SB209670 (a non-selective ET antagonist) or UK 350 926 (a selective ETA receptor antagonist). 3. Volume expansion in untreated obese rats resulted in a blunted cumulative urine sodium excretion (CuUNaV) after 40 min, VE compared with untreated lean rats being 36 and 51% in the denervated and innervated kidneys, respectively (both P < 0.001). 4. In lean rats, both SB209670 and UK 350 926 caused a depressed ability to excrete the saline load and CuUNaV after 40 min, VE compared with untreated being decreased by 51 and 60% in the denervated and innervated kidneys, respectively (both P < 0.001). 5. SB209670 and UK 350 926 given to obese rats reduced (both P < 0.001) CuUNaV after VE by 43% in denervated kidneys compared with untreated obese rats, whereas they were without effect on the magnitude of the excretory response in innervated kidneys. 6. These findings show that the blunted renal excretory responses to VE present in obese rats were not mediated by ET. Conversely, ET, acting through ETA receptors, plays a role as a diuretic and natriuretic factor in maintaining volume homeostasis by, at least in lean rats, renal nerve-independent mechanisms.